Church and Patronage in 20th Century Britain - Webster, Peter. author. aut Link
XII, 256 p. 19 illus., 7 illus. in color.
Keywords: This book is the first full-length treatment of Walter Hussey's work as a patron between 1943 and 1978, first for the Anglican parish church of St Matthew in Northampton, and then at Chichester Cathedral. He was responsible for the most significant sequence of works of art commissioned for the British churches in the twentieth century. They included music by Benjamin Britten, Leonard Bernstein and William Walton, visual art by Henry Moore, Graham Sutherland and Marc Chagall, and poetry by W. H. Auden. Placing Hussey in theological context and in a period of rapid cultural change, it explores the making and reception of the commissions, and the longer-term influence of his work, still felt today. As well as contributing to the religious and cultural history of Britain, and of Anglo-Catholicism and the cathedrals in particular, the book will be of interest to all those concerned with the relationship between theology and the arts, and to historians of music and the visual arts.